The long road to achieving equity: Job accessibility restrictions and overlapping inequalities in the city of São Paulo. (June 2019) - Slovic, Anne Dorothée; Tomasiello, Diego Bogado; Giannotti, Mariana; Andrade, Maria de Fatima; Nardocci, Adelaide C.
Abstract: Access to jobs is an important issue in cities which has not been experienced evenly. The Municipality of São Paulo, one of the world's megacities, reflects this uneven accessibility, marked by urban disparities and segregation of poverty-stricken groups. This study examines the inequalities in job accessibility and how it overlaps with socioeconomic indicators, life expectancy and infrastructure conditions, constituting multiple barriers to the most deprived populations. To capture this data, two extreme ends of the human development index have been selected: below the 10th percentile and above the 90th percentile of the Municipal Human Development Index (MHDI). The level of job accessibility was calculated considering proximity to the public transport network. The public transport network was developed in a Geographic Information System (GIS) environment based on General Transit Feed Specification (GTFS) data and Automatic Vehicle Location (AVL) from buses to measure travel times and to compute accessibility. Additionally, a spatial autocorrelation method considering job accessibility and HDI was applied to better explore the spatially overlapped pattern. Results have showed that lower rates of job accessibility are associated with areas of worse socioeconomic condition, where life expectancy is shorter and infrastructure is disproportionally precarious. In addition to facing longer travel times in public transportation, this lowest HDI percentile faces the overlapping inequalities that prevent their social ascension and inclusion. Highlighting these factors is essential in the search for equity in accessibility and the development of more inclusive transport policies. Highlights: Low MHDI group has lower transit accessibility to jobs than high MHDI group. Low MHDI is mainly non-white, has lower life expectancy, and lives in precarious urban areas than high MHDI group. Spatial mismatch between cities opportunities and low MHDI residence reinforce the overlapping inequalities. Sustainable transport policies should be integrated with land use policies focusing on most vulnerable population.